2018
DOI: 10.3389/fpsyg.2018.01471
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Child Custody Evaluation: A Model for Preliminary Clinical Intervention

Abstract: Intimate partner violence is defined by the World Health Organization as “any behavior within an intimate relationship that causes physical, psychological, or sexual harm to those in the relationship” and it refers to a specific relationship dynamic. In recent decades, an increasing number of studies have focused on this phenomenon, considering its exponential growth over time. Many studies have focused on risk factors for violence within the couple relationship. This paper specifically analyses the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 52 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…While there is a significant body of literature on the efficacy of trauma interventions more broadly (Gennari et al 2018, Lenz et al 2017, Seidler & Wagner 2006, no clinical interventions appear to have been developed specifically for victims of police violence (but see related research on therapy for racist incident-based trauma; Bryant-Davis & Ocampo 2005Carlson et al 2018). In a qualitative study of 40 Black men exposed to police violence and police killings, Lee & Robinson (2019) found that lack of control, defenselessness, and helplessness were prominent among victims, given the inherent power differential and victims' race-based appraisals of this violence (i.e., permanent and something one cannot change).…”
Section: Micro-level Solutions: Addressing the Impact Of Police Viole...mentioning
confidence: 99%
“…While there is a significant body of literature on the efficacy of trauma interventions more broadly (Gennari et al 2018, Lenz et al 2017, Seidler & Wagner 2006, no clinical interventions appear to have been developed specifically for victims of police violence (but see related research on therapy for racist incident-based trauma; Bryant-Davis & Ocampo 2005Carlson et al 2018). In a qualitative study of 40 Black men exposed to police violence and police killings, Lee & Robinson (2019) found that lack of control, defenselessness, and helplessness were prominent among victims, given the inherent power differential and victims' race-based appraisals of this violence (i.e., permanent and something one cannot change).…”
Section: Micro-level Solutions: Addressing the Impact Of Police Viole...mentioning
confidence: 99%